Clinical Outcomes of Infertility Treatment Cycles for Repeatedly Cryopreserved Embryos - Petrushko, Maryna; Piniaiev, Volodymyr; Yurchuk, Taisiia (Problems of Cryobiology and Cryomedicine, 2024)
The study analyzed the survival, re-expansion, and implantation rates of human preimplantation embryos at the blastocyst stage following one and two rounds of cryopreservation using vitrification. Embryos subjected to repeated cryopreservation showed significantly lower survival, re-expansion, and implantation rates compared to those cryopreserved once (р < 0.05 for survival, р < 0.001 for re-expansion and implantation). The highest implantation rate was observed in the group with embryos cryopreserved once (р < 0.001). The results indicate that repeated cryopreservation negatively affects the viability and implantation of embryos, potentially due to structural and functional impairments. These findings highlight the importance of carefully assessing and considering potential risks when planning infertility treatment using repeatedly cryopreserved embryos. Probl Cryobiol Cryomed 2024; 34(3): 236–244